Piloting creative engagement strategies to explore themes of parenthood with fathers - Iryna Culpin; Iryna Culpin; Catherine Lamont-Robinson; Mark Billington; Matthew James; James Prewett; Gareth Ward; Mireia Bes Garcia; Giovanni Biglino; Giovanni Biglino (Frontiers in Child and Adolescent Psychiatry)
IntroductionThe role of the arts in health is increasingly recognised, with participatory arts-based approaches facilitating public engagement. However, little is known about men's involvement in art-based participatory research. We aimed to investigate how men who are fathers may be engaged creatively to explore experiential aspects of fathering and parenthood.MethodsFathers collaborated with an artist, sharing individual perspectives around fatherhood by telephone and email, leading up to creative representations of fatherhood. Initial conversations were prompted by images from a 2020 exhibition catalogue entitled “Masculinities” (Barbican Centre, London) inviting participants' responses to the photographic curation. The catalogue served as an artistic reference to gauge a sense of participants' creative predispositions, as well as a foundation to facilitate spontaneous dialogue about personal meanings of fatherhood. Fathers' experiences of contemporary arts varied greatly; yet all fathers confidently shared responses ranging from photographers' representation of masculinity and fatherhood and perceptions of what was excluded or privileged within this very specific curation. These discussions further led to conversations around representations of fatherhood and highlighted particular areas of interest in terms of fathers' involvement in research and public engagement. The artist provided reflections to each participant by email with links to arts resources building on the initial conversations. Two further shorter sessions followed as fathers' key messages emerged, and the final forms of their own creative expressions crystallised.ResultsThe final pieces included a musical composition around sharing vulnerability as a new father, a word cloud to represent gendered language of parenthood, an animated graphic image representing the bond between father and child, a combination of short poetic stanzas highlighting assumptions around fatherhood, an experiential photographic record of a father and a son in the early years, and a cartoon strip around emotional intelligence in parenting.DiscussionArts-based participatory engagement enabled to capture deep-rooted experiences of being a father in modern society, illuminating common cultural and intergenerational perspectives, while also tapping into unique individual experiences. The richness and diversity of these unique responses suggest that arts-based methodology can facilitate public engagement with men and lead to deep reflections on complex and socially constructed phenomena such as fathering and parenthood.